COMPARISON OF ACTUAL COSTS AND INA-CBGS PACKAGE TARIFFS FOR EPOETIN ALFA COMBINED WITH FOLIC ACID VERSUS EPOETIN ALFA MONOTHERAPY IN CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMODIALYSIS - Ami, Rosi; Seftika Sari; Dwi Endarti (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Chronic kidney disease is a growing health concern, particularly among the elderly population. Anemia therapy in chronic kidney disease patients typically involves the use of epoetin alfa, either alone or in combination with folic acid. However, differences in patient profiles and the alignment between actual treatment costs and INA-CBGs package tariffs remain a challenge in healthcare delivery. This study aimed to analyze the disparity between real costs and INA-CBGs tariffs for hemodialysis therapy. A retrospective cohort design was employed from the health provider’s perspective, analyzing direct medical costs of 73 chronic kidney disease patients undergoing hemodialysis at RSUD Arifin Achmad Pekanbaru between January and March 2025. Data were collected using data collection forms, medical records, and financial reports, and analyzed using univariate methods. The majority of patients were aged ≥45 years (70%) and predominantly male (56.16%), indicating higher prevalence of chronic kidney disease in older adults. The study found that the actual costs of both therapies were substantially higher than the corresponding INA-CBGs package tariffs, highlighting a significant gap between real treatment costs and standardized reimbursement rates.